The effects of inter-trial interval on implicit learning of sequential visual isometric pinch task. Issue 3 (July 2017) - Hashemirad, Fahimeh; Fitzgerald, Paul B.; Zoghi, Maryam; Hashemirad, Masoumeh; Jaberzadeh, Shapour
Abstract: Sequential visual isometric pinch task (SVIPT) has been recently used as a visuomotor sequence task in clinical research. The influence of varying intervals between sequenced trials on the acquisition of implicit sequence learning is not yet determined for SVIPT. The aim of this study was to investigate the effects of inter-trial interval (ITI) on implicit motor sequence learning using SVIPT. A total of 32 healthy participants with mean age 31.3 ± 4.5 years participated in this study. Participants were randomly assigned to one of four ITI groups; (1, 2, 3 and 4 s). They were instructed to control their force on a force transducer to reach a number of targets which appeared on the computer screen by changing the pinch force exerted onto the transducer. In this study, outcome measures were movement time, error rate and skill, which were measured before and after training. Our results indicated that motor sequence learning similarly affected various ITIs. Indeed, all participants exhibited same improvement in implicit learning of SVIPT even though the ITIs varied from 1 to 4 s. Our findings suggest that implicit learning of SVIPT is independent of ITI within this range in healthy individuals.